Goals of care discussions and treatment limitation decisions in European acute geriatric units: a one-day cross-sectional study - Piers, Ruth; Pautex, Sophie; Rexach Cano, Lourdes; Leners, Jean-Claude; Vali Ahmed, Marc; De Brauwer, Isabelle; Kayhan Koçak, Fatma Ö; Hrnciarikova, Dana; Cwynar, Marcin; Alves, Mariana; Pilgram, Erwin H; van Bruchem-Visser, Rozemarijn L (Age and ageing, 2025)
BACKGROUND: It is important to pursue goal-concordant care and to prevent non-beneficial interventions in older people. AIM: To describe serious illness communication and decision-making practices in hospitalised older people in Europe. SETTING/PARTICIPANTS: Data on advance directives, goals of care (GOC) discussions and treatment limitation decisions were collected about patients aged 75-years and older admitted to 23 European acute geriatric units (AGUs). RESULTS: In this cohort of 590 older persons [59.5% aged 85 and above, 59.3% female, median premorbid Clinical Frailty Score (CFS) 6], a formal advance directive was recorded in 3.3% and a pre-hospital treatment limitation in 14.0% with significant differences between European regions (respectively P < 0.001 and P = 0.018).Most prevalent GOC was preservation of function (46.8%). GOC were discussed with patients in 64.0%, with families in 73.0%, within the interprofessional hospital team in 67.0% and with primary care in 13.4%. The GOC and the extent to which it was discussed differed between European regions (both P < 0.001). The prevalence of treatment limitation decisions was 53.7% with a large difference within and between countries (P < 0.001). The odds of having a treatment limitation decision were higher for patients with pre-hospital treatment limitation decisions (OR 39.1), residing in Western versus Southern Europe (OR 4.8), belonging to an older age category (OR 3.2), living with a higher number of severe comorbidities (OR 2.2) and higher premorbid CFS (OR 1.3). CONCLUSIONS: There is large variability across European AGUs concerning GOC discussions and treatment limitation decisions. Sharing of information between primary and hospital care about patient preferences is noticeably deficient.
Keywords: 80 and over; Cross-Sectional Studies; Male; Aging; patient care planning; aged; Europe; Patient Care Planning; pacientova přání ohledně budoucí terapie; Age Factors; plánování péče o pacienty; Aged; Advance Directives; mužské pohlaví; senioři; komunikace; older people; Evropa; geriatrické hodnocení; senioři nad 80 let; lidé; acute hospital; ženské pohlaví; Humans; průřezové studie; věkové faktory; stárnutí; Aged, 80 and over; multicentre study; resuscitation orders; Communication; Female; Geriatric Assessment